A nitric oxide-releasing prodrug promotes apoptosis in human renal carcinoma cells: Involvement of reactive oxygen species - Xie, Jindong; Chen, Lieqian; Huang, Dongqiang; Yue, Weiwei; Chen, Jingyu; Liu, Chunxiao (Open Chemistry, 2021)
JS-K is a nitric oxide (NO)-releasing prodrug of the O2-arylated diazeniumdiolate group that shows pronounced cytotoxicity and antitumor properties in numerous cancer models, including in vitro as well as in vivo. Reactive oxygen species (ROS) induce carcinogenesis by altering the redox status, causing increment in vulnerability to oxidative stress.